Concentrated ambient fine particles exposure affects ovarian follicle development in mice - Mingjun Yang; Fang Tian; Shimin Tao; Minjie Xia; Yuzhu Wang; Jingying Hu; Bin Pan; Zhouzhou Li; Renzhen Peng; Haidong Kan; Yanyi Xu; Weihua Li (Ecotoxicology and Environmental Safety, 2022)
Background: Ambient fine particles (PM2.5) are known to cause various reproductive and developmental diseases. However, the potential mechanisms of PM2.5 exposure induced female reproductive damage remain unclear. Methods: Four weeks old female C57BL/6 J mice were exposed to filtered air (FA, n = 10) or concentrated ambient PM2.5 (CAP, n = 10) using a versatile aerosol concentration enrichment system. After 9 weeks of the exposure, mice were sacrificed under sevoflurane anesthesia and tissue samples were collected. Immunohistochemical analysis, enzyme-linked immunosorbent assay, quantitative polymerase chain reaction, and RNA-sequencing were performed to analyze the effects of PM2.5 exposure on follicle development and elucidate its potential mechanisms. Results: Chronic PM2.5 exposure resulted in follicular dysplasia. Compared to the FA-exposed group, follicular atresia in the CAP-exposed mice were significantly increased. Further studies confirmed that CAP induced apoptosis in granulosa cells, accompanied by a distortion of hormone homeostasis. In addition, RNA-sequencing data demonstrated that CAP exposure induced the alteration of ovarian gene expressions and was associated with inflammatory response. Conclusions: Chronic exposure to CAP can induce follicular atresia, which was associated with hormone modulation and inflammation.